37-5x=3(1+7x)+8x

Simple and best practice solution for 37-5x=3(1+7x)+8x equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 37-5x=3(1+7x)+8x equation:



37-5x=3(1+7x)+8x
We move all terms to the left:
37-5x-(3(1+7x)+8x)=0
We add all the numbers together, and all the variables
-5x-(3(7x+1)+8x)+37=0
We calculate terms in parentheses: -(3(7x+1)+8x), so:
3(7x+1)+8x
We add all the numbers together, and all the variables
8x+3(7x+1)
We multiply parentheses
8x+21x+3
We add all the numbers together, and all the variables
29x+3
Back to the equation:
-(29x+3)
We get rid of parentheses
-5x-29x-3+37=0
We add all the numbers together, and all the variables
-34x+34=0
We move all terms containing x to the left, all other terms to the right
-34x=-34
x=-34/-34
x=1

See similar equations:

| Y=18(0.15)*x | | 1/8g+7=g | | 10x^2+27x-288=0 | | -5(r+8)=-67 | | 5x/3-3=17 | | 8(4-7x)+8(x+2)=0 | | 7y=2y-55 | | 8x-(4x+5)=5x-25 | | -209=6+5(-8v-3) | | 5c–2(c–5)=17 | | 57=3.8x | | f(5)=2(3.14)(5^3) | | 2(6k+4)+5(1+5k)=50 | | 2(2-3x)=2(5x+1) | | 72=4(x-5) | | x÷0.6=8.9 | | (4x+2)÷(6x+3)=0 | | (x+9)=(3x-33) | | 84=2.1x | | 29x=23x=42 | | 0x+1=3x+4 | | -65=-8(5x-5)+5(7+x) | | 24=5+k | | 3b-4=-5b+20 | | 4/7*y=12 | | X+(x+2)+(x+2)=186 | | 5x+(2x-7)=23 | | X2=4x+21 | | 3n+2=1/ | | 5(7x-1)=49 | | 1/4x-1/5=3/4x+2 | | 3×+7=8x-1 |

Equations solver categories